2014
DOI: 10.1007/s11064-014-1448-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of N-Acyl 5-Hydroxytryptamines on Glutamate-Induced Cytotoxicity in HT-22 Cells

Abstract: Some endocannabinoids have been known to express anti-inflammatory and antioxidant actions independent of cannabinoid receptors. In this respect, we investigated whether N-acyl 5-hydroxytryptamines (5-HTs) might prevent against glutamate-induced oxidative cytotoxicity in HT-22 cells, and attempted to elucidate the mechanism for their cytoprotective action. N-acyl 5-HTs with palmitoyl, stearoyl, arachidonoyl or docosahexaenoyl chain expressed a remarkable protective effect on glutamate-induced cytotoxicity. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 42 publications
4
50
0
Order By: Relevance
“…N-acyl phospholipids are considered aytipical lipids implicated in the biosynthesis of lipid mediators such as endocannabinoids. In parallel, it has been shown that phenolic endocannabinoids like N-acyl 5-HT, present in the brain exert a cytoprotective action against glutamateinduced oxidative damage of HT-22 cells possibly by an Nrf2-mediated mechanism (Jin et al, 2014).…”
Section: Nrf2 and Lipid Metabolismmentioning
confidence: 99%
“…N-acyl phospholipids are considered aytipical lipids implicated in the biosynthesis of lipid mediators such as endocannabinoids. In parallel, it has been shown that phenolic endocannabinoids like N-acyl 5-HT, present in the brain exert a cytoprotective action against glutamateinduced oxidative damage of HT-22 cells possibly by an Nrf2-mediated mechanism (Jin et al, 2014).…”
Section: Nrf2 and Lipid Metabolismmentioning
confidence: 99%
“…It prevented the convulsion in mice administered with pentylenetetrazole [27] , enhanced anxiolytic behavior in the elevated plus maze (EPM) in mice at basolateral amygdale [28] , reduced carrageenan-induced hyperalgesia in mice [29] and decreased anxiety-like behavior in EPM [30] . Recently, NA-5HT was observed to possess anti-allergic and anti-inflammatory actions in mast cells [13,14] . Very recently, NA-5HT was observed to show antioxidant action through activation of Nrf2 signaling in HT-22 cells [14] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that N -acyl 5HTs exerted a potent antioxidant action by inducing antioxidant enzymes via the activation of PI3K/Akt signaling in HT-22 cells [14] . In this regard, we examined whether NA-5HT could affect the expression of representative antioxidant enzymes such as GCLC, HO-1 and NQO-1, which were known to suppress oxidative stress [16] .…”
Section: Regulatory Effect Of Na-5ht On Induction Of Antioxidant Enzymentioning
confidence: 99%
See 2 more Smart Citations